Decitabine-Mediated Upregulation of CSPG4 in Ovarian Carcinoma Cells Enables Targeting by CSPG4-Specific CAR-T Cells - Harrer, Dennis Christoph; Schenkel, Charlotte; Berking, Carola; Herr, Wolfgang; Abken, Hinrich; Dörrie, Jan; Schaft, Niels (Cancers, 2022)
Simple Summary Cancer therapy by specifically redirected T cells has revolutionized the field of oncology. However, the repertoire of targetable antigens is small. Here, we use the FDA-approved drug decitabine to upregulate the surface antigen CSPG4 on CSPG4-negative ovarian carcinoma cells. By optimizing decitabine dosing, we converted more than 50% of treated ovarian carcinoma cells to CSPG4-positive cells. Importantly, CSPG4 is a very well-established target antigen in melanoma, and we could previously demonstrate that T cells engineered to target CSPG4 could reliably kill CSPG4-positive melanoma cells. Using CSPG4-specific T cells, we demonstrate CSPG4-directed killing of decitabine-treated ovarian carcinoma cells, thereby adding CSPG4 to the repertoire of target antigens for ovarian cancer. The addition of CAR-T cells to the armamentarium of immunotherapy revigorated the field of oncology by inducing long-lasting remissions in patients with relapsing/refractory hematological malignancies. Nevertheless, in the lion's share of patients diagnosed with solid tumors, CAR-T-cell therapy so far failed to demonstrate satisfactory anti-tumor activity. A crucial cause of resistance against the antigen-specific attack of CAR-T cells is predicated on the primary or secondary absence of suitable target antigens. Thus, the necessity to create a broad repertoire of different target antigens is vital. We aimed to evaluate the potential of the well-established melanoma antigen chondroitin sulfate proteoglycan 4 (CSPG4) as an inducible antigen in ovarian cancer cells, using CSPG4-negative SKOV-3 ovarian cancer cells as a model. Based on the hypomethylating activity of the FDA-approved drug decitabine, we refined a protocol to upregulate CSPG4 in the majority of decitabine-treated SKOV-3 cells. CSPG4-specific CAR-T cells generated by mRNA-electroporation showed CSPG4-directed cytokine secretion and cytotoxicity towards decitabine-treated SKOV-3. Another ovarian cancer cell line (Caov-3) and the neoplastic cell line 293T behaved similar. In aggregate, we generated proof-of-concept data paving the way for the further exploration of CSPG4 as an inducible antigen for CAR-T cells in ovarian cancer.
CRIS-Team WoS Importer:2022-11-11